Tinjauan Yuridis Penelantaran Tanah di Provinsi Jawa Barat Dikaitkan dengan Peraturan Pemerintah Nomor 11 Tahun 2010 Tentang Penertiban dan Pendayagunaan Tanah Terlantar - Ida Kurniasih (Universitas Islam Nusantara, 2019)
Most abandoned or abandoned land is a land for business use rights owned by state-owned companies or private companies. In practice, many lands are abandoned or abandoned so that many people occupy it either with permission or without permission from the owner. Other land abandonment also hampered the achievement of various development program objectives, vulnerability to food security and national economic resilience, the closed social economic access of the community, especially farmers to land, and the nagging sense of justice and social harmony, Rights Holders are prohibited from abandoning their land, and if The Right Holder abandoned his land so that the (Law No. 5 Th 1960) has regulated the legal consequences of the abolition of the land rights in question and the termination of legal relations and confirmed as land directly controlled by the State. Based on this background, the researcher will discuss the main issues as follows: What are the Legal Aspects of land rights that have been granted rights by the State but are not attempted and / or not used, or not utilized in accordance with the circumstances or the nature and purpose of givingrights or basic tenure ? How the efforts to control and utilize abandoned land are reviewed from GovernmentRegulation Number 11 of 2010 concerning Control and Utilization of abandoned land.